Life-Threatening Intracerebral Hemorrhage in Adult with ITP: Challenging Entity - Diyora, Batuk; Purandare, Anup; Devani, Kavin; Kale, Pramod; Shah, Vikrant; Patankar, Roy (Asian Journal of Neurosurgery, 2023)
Intracerebral hemorrhage (ICH) is a rare and fatal complication of immune thrombocytopenia. ICH is more common in children than in the adult population. A 30-year-old male patient, a known case of immune thrombocytopenia, presented with sudden onset severe headache and vomiting. Computed tomography scan showed a large right frontal intracerebral hematoma. His platelet counts were low, and he received multiple transfusions. Though he was initially conscious, his neurological condition progressively deteriorated, so the decision was taken for an emergency craniotomy. Despite multiple transfusions, his platelet counts were 10,000/µL, so craniotomy was very risky. He underwent an emergency splenectomy and received one unit of single donor platelets. Subsequently, his platelets count increased a few hours after, and he underwent successful evacuation of intracerebral hematoma. He eventually had an excellent neurological outcome. Though intracranial hemorrhage carries significant morbidity and mortality, a timely decision of emergency splenectomy followed by craniotomy can result in an excellent clinical outcome.
Keywords: intra cerebral hemorrhage; ITP; craniotomy; splenectomy